1975
DOI: 10.1016/0042-6989(75)90291-6
|View full text |Cite
|
Sign up to set email alerts
|

Opponent process additivity—II. Yellow/blue equilibria and nonlinear models

Abstract: Abstract-A yellow/blue equilibrium Iight is one which appears neither yellowish nor bluish (i.e. uniquely red, uniquely green, or achromatic). The spectral locus of the monochromatic greenish equilibrium (around 500 nm) shows little, if any, variation over a luminance range of .! log,, units. Reddish equilibria are extraspectral. involving mixtures of short-and long-wave light. Their wavelength composition is noninvariant with luminance: a reddish equilibrium light turns bluish-red if luminance is increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
2

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(41 citation statements)
references
References 8 publications
7
31
2
Order By: Relevance
“…40 However, in a variation of that theory, M-cones can also contribute to blueness via a nonlinear contribution to the Y/B pathway, the strength of which depends on adapting condition and observer. 41 This general hypothesis is also consistent with our data. A reviewer kindly suggested a further possibility, that M-cones can contribute to a variety of hues by stimulating one or other "higher-order" color mechanism, 42 depending on the condition.…”
Section: Implications For Color Theorysupporting
confidence: 82%
“…40 However, in a variation of that theory, M-cones can also contribute to blueness via a nonlinear contribution to the Y/B pathway, the strength of which depends on adapting condition and observer. 41 This general hypothesis is also consistent with our data. A reviewer kindly suggested a further possibility, that M-cones can contribute to a variety of hues by stimulating one or other "higher-order" color mechanism, 42 depending on the condition.…”
Section: Implications For Color Theorysupporting
confidence: 82%
“…The extent to which these spectral sensitivities are nonlinear, and the conditions under which these nonlinearities are manifest, remain unclear. 51,52,[57][58][59][60] However, individual differences in color appearance based on different linear cone combinations predict stronger dependence for the binary hues than we observed, for in that case the spectral sensitivities are completely determined by and covary with the focal direction.…”
Section: Discussioncontrasting
confidence: 47%
“…Linear expressions provide acceptable fits to the experimentally determined hue cancellation functions upon which the quantitative model was originally based; hence, they are used in this presentation. Outcomes of experimental tests by a number of investigators are consistent with linearity for the red/green chromatic channel, although for the yellow/blue channel departures from linearity have been found that seem to vary in degree from one observer to the next (16)(17)(18)(19)(20). Because the test measures used as the index of adaptation and recovery in the experiments reported here involve only the red/green system, we can accept the linear relation as an adequate.…”
Section: Discussionmentioning
confidence: 70%